Active and Recyclable Polyethylene‐Supported Iridium‐(N‐ Heterocyclic Carbene) Catalyst for Hydrogen/Deuterium Exchange Reactions. Issue 14 (13th July 2016) - Romanenko, Iuliia; Norsic, Sébastien; Veyre, Laurent; Sayah, Reine; D'Agosto, Franck; Raynaud, Jean; Boisson, Christophe; Lacôte, Emmanuel; Thieuleux, Chloé
Abstract: The multistep synthesis of a polyethylene‐supported iridium(III)‐(N‐heterocyclic carbene) hydrogen/deuterium exchange catalyst was performed starting from an iodo‐polyethylene obtained via catalyzed polyethylene chain growth (CCG) on magnesium. Unique thermomorphic polyethylene properties give the possibility to perform catalytic hydrogen/deuterium exchange reactions at 100 °C in the homogeneous phase with simple catalyst separation as a precipitate at room temperature. The catalytic activity of the polymer‐supported catalyst was compared with that of its monomeric analogue. The catalytic studies showed that the supported catalyst exhibits similar profiles and turnover numbers as homogeneous counterparts without deactivation. Abstract :